2007
DOI: 10.1021/cr050948h
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis in Ionic Liquids

Abstract: Pa ˆrvulescu and Hardacre Scheme 80. Thioacetalization and Transthioacetalization of Aromatic Aldehydes Scheme 81. Ethylenediammonium-Diacetate-Catalyzed Gewald Synthesis of 2-Aminothiophenes Scheme 82. Preparation of Bis-indolylmethanes through Electrophilic Substitution Reactions of Indoles with Aldehydes and Ketones in ILs Scheme 83. Conversion of Ethyl Cyclohexanone-2-carboxylate to Methyl Vinyl Ketone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
1,096
0
13

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,236 publications
(1,141 citation statements)
references
References 520 publications
6
1,096
0
13
Order By: Relevance
“…2,3 Due to their outstanding features, ILs have been studied as more environmentally benign solvent media in a large number of applications, such as in organic and inorganic synthesis, catalysis, polymerization, and separation/extraction processes. [4][5][6][7][8] The motivation behind the booming research on ILs is not only a result of their excellent properties, 9 but also an outcome of their tuneable character. Their physicochemical properties can be tailored to suit a specific function by changing their ion chemical structures, including the incorporation of functionalized groups; thus, they are often referred to as "designer solvents".…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Due to their outstanding features, ILs have been studied as more environmentally benign solvent media in a large number of applications, such as in organic and inorganic synthesis, catalysis, polymerization, and separation/extraction processes. [4][5][6][7][8] The motivation behind the booming research on ILs is not only a result of their excellent properties, 9 but also an outcome of their tuneable character. Their physicochemical properties can be tailored to suit a specific function by changing their ion chemical structures, including the incorporation of functionalized groups; thus, they are often referred to as "designer solvents".…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [4][5][6][7][8] have shown that all of the components of biomass are soluble in ionic liquids (ILs), salts that are liquid below 373 K and are green solvent candidates for a number of applications. [9][10][11][12][13] The viscosity of such solutions rises rapidly with biomass dissolution, making it difficult to pump such solutions and causing a reduction in mass transfer rates. As a consequence, there is an interest in understanding how the viscosity of ionic liquids change with the dissolution of carbohydrates and what can be done to reduce the viscosity of such solutions by the addition of a cosolvent.…”
Section: Introductionmentioning
confidence: 99%
“…The use of IL is of high current interest for catalysis (Parvulescu and Hardacre 2007), biocatalysis and other applications are emerging. ILs are often discussed as the alternative to organic solvents in view of sustainable and ultimately "green" processes.…”
Section: Introductionmentioning
confidence: 99%